REGIONAL ANESTHESIA IN MOLAR PREGNANCY WITH THYROTOXICOSIS IN A REMOTE HOSPITAL - Ryalino, Christopher; Aryasa, Tjahya; Budiarta, I Gede; Senapathi, Tjokorda Gde Agung (Bali Journal of Anesthesiology, 2017)
Hydatidiform mole or molar pregnancy is a benign Gestational Trophoblastic Disease (GTD) that originates from the placenta. Treatment consists of vacuum evacuation but rarely hysterectomy may be required. One common complication of molar pregnancy is hyperthyroid. Anesthetic management is often complicated by the associated systemic complications. These complications cannot be prevented, but with a better understanding of the disease, some measurements to avoid maternal mortality can be performed.Â Â